The efficacy and tolerability of the slow-acting combined agent glucosamine and chondroitin sulfate in gonarthrosis patients tacking no nonsteroidal anti-inflammatory drugs - A. P. Rebrov; I. A. Romanova; I. Z. Gaydukova (Современная ревматология)
Objective: to evaluate the efficacy and tolerability of the combined symptomatic slow-acting combined agent Theraflex in gonarthrosis patients untreated with nonsteroidal antiinflammatory drugs (NSAIDs).Patients and methods. The investigation enrolled 84 patients (78 women and 6 men) aged 55.23±7.36 years with knee arthritis lasting 6.2±0.98 years who were blindly randomized into 2 groups. A study group took Theraflex (chondroitin sulfate 400 mg and glucosamine sulfate 500 mg) with or without acetaminophen. A comparison group received acetaminophen only. At baseline and 3 and 6 months after treatment, the investigators assessed changes in the magnitude of osteoarthritis (OA) using WOMAC and Lequen's indices, evaluated the therapeutic efficiency rated by a patient and a physician according to the visual analogue scale, and took into account adverse reactions (AR).Results. All the patients taking Theraflex for 6 months showed a positive effect in substantially lowering WOMAC and Lequen's indices and reducing pain and needs for analgesics as compared to both the values at baseline and those obtained in the patients receiving acetaminophen only.Conclusion. In osteoarthritis patients untreated with NSAIDs, Theraflex treatment was associated with a reduction in pain syndrome and stiffness and with better function and lower needs for analgesics. Six-month Theraflex therapy did not cause serious ARs, as well as in patients having controlled gastrointestinal and renal diseases and hypertension